A agroecologia como orientação política no MST: caminho para emancipação nacional popular ou para o transformismo? - Maranho, Fernanda Peres (2019)
From the gramscian theoretical framework, we propose the analysis of the Agrarian reform project formulated by the MST, especially its recent re-signification represented by the adjective "Popular" accompanied by a new matrix of production: agroecology. For this, the concepts of national-popular collective will, passive revolution and transformism, formulated by Gramsci in the Prison notebooks, support the research in the perspective that the process of transition to the new productive matrix can be read while a deepening in the construction of the autonomy of the Movement as the organizer of expressive plots of the subaltern classes in the countryside, while its political alignment with the government of a historic ally, the PT, determines relations, commitments and trajectories that bring it closer to transformism. For this, we seek in the literature and in the documentation produced by the MST, through a theoreticalpolitical and historical approach of the “objective and subjective” conditions, to shed light on the relations of force involved in the national construction of its Agrarian reform project, as well as about the ways and obstacles for its implantation. In this sense, we consider both the structural obstacles that overlap the development of the project and the contributions it offers in an innovative way.